Hubungan Anemia dan KEK pada Ibu Hamil dengan Kejadian Bayi Baru Lahir Rendah (BBLR) di Puskesmas Landasan Ulin Timur Tahun 2023 - Annisa Kharimah; Hairiana Kusvitasari; Novita Dewi Iswandari (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2025)
Background: Based on Indonesian health profile data, the cause of neonatal deaths is low birth weight (LBW) babies, namely 7150 (35.3%) cases. Factors that influence the incidence of LBW are malnutrition status during pregnancy from chronic energy deficiency (CED) and maternal anemia. The Landasan Ulin Timur Community Health Center in 2022 will be the 2nd highest in anemia at 30.1% and KEK for pregnant women at 15.30% and the incidence of LBW is high. Objective: To analysis the relationship between anemia and CED in pregnant women with the incidence of low birth weight (LBW) babies at the Landasan Ulin Timur Health Center in 2023. Method: Research design with Retrospective Case Control Study. The population is all newborn babies in 2023, there are 348 babies with a total sampling technique for the case group, there are 26 LBW babies and the control group is simple random sampling, there are 26 babies. Test analysis with univariate and bivariate chi-square. Results: There was a history of anemia among 52 pregnant women in 12 mothers (23.1%) and CED in 11 mothers (21.2%). The relationship between anemia and LBW was found to be a p-value of 0.021 (p<0.05) and an Odd Ratio (OR) of 7.500, the relationship between KEK and LBW was found to be a p-value of 0.042 (p<0.05) and OR 6.353. Conclusion: There is a relationship between anemia and a 7 times higher risk of experiencing LBW, while there is a relationship with CED with a 6 times higher risk of experiencing LBW. It is hoped that health workers can pay attention to the causes of LBW and can take early prevention.